Gestão sustentável dos resíduos sólidos na rede municipal de ensino de Foz do Iguaçu PIC - Programa de Incentivo à Compostagem - Teixeira, Sandra Soares (2014)
This work was to develop a thematic program for sustainable solid waste management for municipal schools of Foz do Iguaçu, based on the National Policy on Solid Waste - Law 12.305/12, aims to work every step of the waste chain, promote selective collection and direct organic solid waste that is generated daily in these educational institutions to use via the composting process. Held at the Municipal School President Getulio Vargas of Foz do Iguaçu, with teachers and elementary students; this study demonstrated the importance of effective waste management in this scenario, as well as prioritize the minimization of environmental impacts contributes to society by ensuring educational gains, also social and economic. Based on this premise that the PIC - Composting Incentive Program aims to reach people involved in the process, making the multiplier environmental awareness.